Synchronization of directed switched complex networks with stochastic link perturbations and mixed time-delays. (February 2018) - Liu, Yurong; Wang, Zidong; Ma, Lifeng; Cui, Ying; Alsaadi, Fuad E.
Abstract: In this paper, the synchronization problem is studied for a class of directed switched complex networks. The links among the nodes are perturbed by stochastic noises and the topology varies according to certain predetermined switching rules. The coupled networks under consideration are subject to mixed delays comprising both discrete and distributed ones. A new estimate of the general algebraic connectivity is firstly given for the directed complex networks, based on which the exponential synchronization problem is analyzed by virtue of the average-dwell-time technique. Then, sufficient conditions are derived to guarantee the synchronization in mean square provided that the switching is slow on the average. Subsequently, the switched complex networks with link failures are investigated and it is shown that the synchronization can be achieved if the average link failure ratio does not exceed certain threshold. Finally, a numerical simulation example is presented to demonstrate the effectiveness of the proposed algorithm.